Effect Of sodium Benzoate and Citric Acid on the Quality of Jack Fruit (Artocarpus heterophyllus Lmk.) Juice during Storage - M. Maman Rohaman; Suhadi Hardjo (Balai Besar Industri Agro, 1986)
The effect of sodium benzoate and citric acid to the quality of jack fruit juice during storage has been studied. The concentration of sodium benzoate used were; 500 and 1000 ppm, while citric acid were 0;0.1 and 0.2 percent. The result showed that sodium benzoate significantly affect the total acid, pH and total microbial count. The higher the sodium benzoate concentration, the lower the total acid will be, while the pH will increase and total microbial count decrease. The addition of citric acid resulted in the decrease of total acid and vitamin C, while the PH increase. Vitamin C content, pH, total soluble solid and viscosity decreased during storage and total microbial count increase. Organoleptic test showed that the addition of 0.1 percent citric acid is acceptable.